(3GdCfSGHs - (3GdSeYGfj , YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj GdTGaYj GdMGaX, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3GHf CHj MGQKI RgjQ Hf MPjaI YHSjGf bGd hHYO s
(3BNQgG (B:s
(3GHf YHjO Gddg Hf jMji hHGdHQI GHG YeQ eMeO Hf eMeO Hf eMeO Hf HcQ GdgRGfi s
(3bWYI CNQi ef GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B4s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B329 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B36 s
Keywords: (3GdJGQjNs